Analisis Faktor-Faktor yang Mempengaruhi Hasil Produksi Padi Desa Sungai Batang Kecamatan Martapura Barat Kabupaten Banjar - Ainy, Intan Novera Qurotul; Eny Fahraty (PPJP ULM, 2019)
This study aims to determine: (1) Effect of land area, seeds, fertilizers, pesticides and labor on rice production, (2) The most dominant factor influences rice production, (3) the state of return to scale rice production in Sungai Batang Village. The population of this study was rice farmers in Sungai Batang Village. The samples taken in this study were 84 rice farmers. Data collection techniques are by conducting literature studies, observations, distribution of questionnaires and interviews. The data analysis technique is by classical assumption test and using multiple linear regression analysis methods. The results showed that the land area, seeds, fertilizers, pesticides and labor together (simultan) had a positive and significant effect on rice production.This is evidenced by f- statistics> f-table (56,7> 2.21). Land area, seeds, fertilizers and labor have a positive and significant effect, while pesticides do not have a significant effect. Return to scale on rice production shows constant return to scale because the number of coefficients of each variable isequal to 1%.